2018
DOI: 10.1038/s41598-018-31987-1
|View full text |Cite
|
Sign up to set email alerts
|

Subtropical adaptation of a temperate plant (Brassica oleracea var. italica) utilizes non-vernalization-responsive QTLs

Abstract: While many tropical plants have been adapted to temperate cultivation, few temperate plants have been adapted to the tropics. Originating in Western Europe, Brassica oleracea vernalization requires a period of low temperature and BoFLC2 regulates the transition to floral development. In B. oleracea germplasm selected in Taiwan, a non-vernalization pathway involving BoFLC3 rather than BoFLC2 regulates curd induction. In 112 subtropical breeding lines, specific haplotype combinations of BoFLC3 and PAN (involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…10). We detected several previously described SVs in B. oleracea, including the two indels in BoFLC3 related to subtropical adaptation of broccoli (Lin et al, 2018), and the two indels in BoFRIa related to winter annual or biennial habit of cauliflower and cabbage (Irwin et al, 2012).…”
Section: Svs Between Genomes Of Korso and Ox-heartmentioning
confidence: 64%
See 2 more Smart Citations
“…10). We detected several previously described SVs in B. oleracea, including the two indels in BoFLC3 related to subtropical adaptation of broccoli (Lin et al, 2018), and the two indels in BoFRIa related to winter annual or biennial habit of cauliflower and cabbage (Irwin et al, 2012).…”
Section: Svs Between Genomes Of Korso and Ox-heartmentioning
confidence: 64%
“…The MADS box transcription factor FLC, a flowering time integrator in the vernalization and autonomous pathways, acts as a repressor of flowering (Michaels and Amasino, 1999;Sheldon et al, 1999). Several studies have demonstrated the roles of FLC paralogues in flowering time in diverse B. oleracea morphotypes (Okazaki et al, 2007;Razi et al, 2008;Ridge et al, 2015;Irwin et al, 2016;Lin et al, 2018). A 3,371-bp insertion (SV_b_92666a) in the promoter of BoFLC1.1 in Korso was found under strong differential selection, present in 99% and 88% of the cauliflower and broccoli accessions, respectively, while only in 9% of cabbage accessions (Fig.…”
Section: Transition From Vegetative To Generative Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The DH based breeding populations have been instrumental in discovery and mapping of QTLs of economically important agronomic and quality traits in Brassica vegetables [35, 51, 72, 89]. DH based populations has also facilitated the construction of high-density genetic linkage map [90], mapping QTLs/genes for disease resistance [50, 70], identification of QTLs related to timing of curd induction, subtropical adaptation in Brassica oleracea crops [35, 46, 62]. Thus, realizing the utility of DH technology in accelerating the genetic improvement of B. oleracea crops, completely homozygous DH lines have been developed by our group previously through IMC in cauliflower [7-9].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study indicated that BoFLCs polymorphisms existed in Brassica genus crops. The expression of Flowering Locus C (FLC) in Brassica oleracea includes BoFLC3 in broccoli (Lin et al, 2018) and BoFLC4 in cabbage (Lin et al, 2005). However, in Chinese kale and broccoli, BoFLC5 does not contribute to flowering time because of premature stop codons (Razi et al, 2008).…”
mentioning
confidence: 99%